The Relationship Between Strategic Improvisation And Entrepreneurial Performance: Analytical Research In The Ministry Of Agriculture - SAIHOOD, AHMED QASIM; ADEL –JADER, DR. SUHAIR (The journal of contemporary issues in business and government, 2021)
The main objective of the research is to investigate the relationship and influence between strategic improvisation and entrepreneurial performance in the Ministry of Agriculture and to identify the nature and patterns of thinking prevailing at the leadership levels in the concerned ministry in order to identify appropriate procedures and practices that work to establish a culture of strategic improvisation and direct it towards enhancing entrepreneurial performance. Data were collected from (147) respondents represented by an intentional sample of the administrative leaderships and for data analysis, statistical programs (SPSS, AMOS) were employed by adopting appropriate statistical methods, and the results showed the correctness of correlations and influence at the level of major variables and sub-dimensions, which indicates the essential role of strategic improvisation to achieve entrepreneurial performance in the Ministry of Agriculture.